Le living lab, un intermédiaire d’innovation ouverte pour les territoires ruraux ou péri-urbains ? - Fasshauer, Ingrid; Zadra-Veil, Cathy (Innovations, 2020)
L’objectif de cet article est d’analyser une nouvelle forme organisationnelle, le living lab (LL) et sa capacité à favoriser l’innovation territoriale en milieu rural ou péri-urbain. A travers une revue de littérature et la mobilisation de la sociologie de l’acteur-réseau (Callon, 1986 ; Latour, 1987), nous positionnons les living labs comme intermédiaires d’innovation ouverte dont les caractéristiques permettent d’intégrer de nombreux acteurs hétérogènes, établissements publics, entreprises privées, associations et citoyens, sur des projets d’innovation. L’étude d’un LL rural met en évidence la capacité d’une telle structure à reconfigurer des réseaux d’acteurs pour proposer une série de tiers-lieux adaptés aux spécificités des territoires sur lesquels ils s’implantent. Cette recherche permet d’enrichir la réflexion la pérennisation des tiers-lieux ruraux et leurs spécificités par rapport aux espaces urbains.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: De Boeck Supérieur
Keywords: Collaboration; Innovation; Innovation ouverte; Laboratoire vivant; Living Labs; Réservé UdeM; Économie collaborative

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Number: 4
Keywords: Collaboration; Durabilité; Europe; Hackathon; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Médialab; Technologies; numérique